Algorithms and law - Ebers, Martin; Navas, Susana (UK, CUP, 2020)
"Algorithms come in many different shapes and forms, ranging from software systems (e.g. data mining programs, medical diagnosis systems, price algorithms and expert trading systems) to embodied robots (e.g. self-driving cars, unmanned underwater vehicles, surgical robots, drones, personal and social robots) and open source machine learning systems.1 The increased use of these intelligent systems is changing our lives, our society, our economy - challenging at the same time the traditional boundaries of law. Algorithms are widely employed to make decisions that have increasingly far-reaching impacts on individuals and the society, leading potentially to manipulation, biases, censorship, social discrimination, violations of privacy, property rights, and more"--
Includes bibliographical references and index.
Keywords: Artificial intelligence -- Robotics; Computer networks; Robotics; Information storage and retrieval systems; Law